Optimalisasi Pojok Literasi TK Bhakti Husada Magelang, Tumbuhkan Kebiasaan Anak Indonesia Hebat - Ikaningrum, Rini Estiyowati; Indriani, Lilia; Aryanti, Zahra Nurmadina; Febriyanti, Febe (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
To enhance the quality of early childhood education, teachers play a vital role in fostering reading interest and shaping positive habits through engaging literacy activities. However, many teachers still face challenges in optimizing literacy facilities in schools. Based on this condition, this community service program was implemented at TK Bakti Husada Magelang with the aim of assisting early childhood educators in utilizing the literacy corner as a medium to enhance children’s literacy skills and develop the 7 Habits of Great Indonesian Children. The program was implemented through four stages observation, socialization, mentoring, and evaluation using various methods such as teacher training, shared reading sessions, creative workshops, educational games, and regular monitoring of children’s progress. The results showed an improvement in teachers’ skills in managing engaging literacy activities, an increase in reading interest among children, and the gradual formation of seven positive habits that reflect the character of great Indonesian children. Therefore, this mentoring activity contributes significantly to optimizing the role of the literacy corner as a medium for developing literacy and character among early childhood students at TK Bakti Husada Magelang.